2019
DOI: 10.3847/1538-4357/ab0c9d
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Reversal of Breakout Reconnection Preceding a Jet: Evidence of Oscillatory Magnetic Reconnection?

Abstract: Recent studies have revealed that solar jets involving minifilament eruptions may be initiated under the well-known magnetic-breakout mechanism. Before or just at the onset of those jets, there should be a current sheet, where breakout magnetic reconnection takes place, between open fields and the outside of the jet-base arcade carrying minifilament in its core. In this paper we present a jet produced by eruption of two minifilaments lying at the jet base. A current sheet is directly detected near the jet base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…Subarcsecond plasmoids were detected by the IRIS, whose average size is about 0.57 Mm, and their ejecting speed ranges from 10 to 220 km s −1 [135]. Besides the observation of plasmoids in straight anemone jets [81,[136][137][138][139], they were also observed in two-sided-loop jets [44] (figure 4). Analysis results indicated that plasmoids observed in different types of jets were similar, and they were thought to be created by magnetic reconnection as a result of the tearing instability of the current sheets.…”
Section: (Ii) Plasmoidmentioning
confidence: 97%
“…Subarcsecond plasmoids were detected by the IRIS, whose average size is about 0.57 Mm, and their ejecting speed ranges from 10 to 220 km s −1 [135]. Besides the observation of plasmoids in straight anemone jets [81,[136][137][138][139], they were also observed in two-sided-loop jets [44] (figure 4). Analysis results indicated that plasmoids observed in different types of jets were similar, and they were thought to be created by magnetic reconnection as a result of the tearing instability of the current sheets.…”
Section: (Ii) Plasmoidmentioning
confidence: 97%
“…Such cancelation and the resulting formation and eruption of small-scale ("mini") filaments has been proposed as driving mechanism for many coronal jets that feed into the solar wind (Sterling et al, 2015). Recent IRIS/SJI and SDO observations have been used to provide support for this mechanism (Hong et al, 2019) through imaging of the evolution of the predicted break-out current sheet that precedes the eruption of a mini-filament and jet.…”
Section: Mass Supply To the Solar Windmentioning
confidence: 99%
“…Generally, the fan-spine magnetic system represents the 3D magnetic topology of straight anemone type solar jets Shen (2021), and many observational and numerical simulation works are all taken such a special magnetic system as the basic coronal magnetic environment of solar jets (e.g., Pariat et al 2009;Sterling et al 2015;Wyper et al 2018;Shen et al 2019a;Hong et al 2019). Many recent high spatiotemporal resolution observations showed that solar jets are driven by mini-filament eruptions in fan-spine systems and in association with photospheric magnetic flux cancellations, and these features are also frequently observed in largescale energetic solar eruptions (e.g., Shen et al 2012aShen et al , 2017Sterling et al 2015;Hong et al 2016Hong et al , 2017Wyper et al 2017;Panesar et al 2017Panesar et al , 2018Sterling et al 2018;Samanta et al 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%